Contemporary Left Main Percutaneous Coronary Intervention: A State-of-the-art Review - Refai Showkathali; Radha Priya Yalamanchi (Interventional Cardiology: Reviews, Research, Resources)
The majority of the left ventricular myocardium is supplied by the left main coronary artery. Atherosclerotic obstruction of the left main coronary artery therefore leads to significant myocardial jeopardy. Coronary artery bypass surgery (CABG) has been the gold standard for left main coronary artery disease in the past. However, advancements in technology have established percutaneous coronary intervention (PCI) as a standard, safe and reasonable alternative to CABG, with comparable outcomes. Contemporary PCI of left main coronary artery disease comprises careful patient selection, accurate technique guided by either intravascular ultrasound or optical coherence tomography and – if necessary – physiological assessment using fractional flow reserve. This review focuses on current evidence from registries and randomised trials comparing PCI with CABG, procedural tips and tricks, adjuvant technologies and the triumph of PCI.